Małecki epizod biografii Andrzeja Frycza Modrzewskiego. Przyczynek do badań dziejów „małej ojczyzny" pisarza - Wichowa, Maria (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
The studies titled “Małecki episode of Andrzej Frycz Modrzewski biography.” The contribution to the research on “the small homeland” of the writer contains information about history of the village, which history was coagulated by the outstanding political writer of Polish Renaissance at the end of his life and in which country he found the place of the eternal rest. The connection between the house of Korycińscy and humanists environement in particular - Andrzej Frycz Modrzewski has especially been emphesized. The lots of Renaissance gravestones of Adam and Maciej Koryciński, which lots were based on the archival materiales unknown up to now, have also been introduced.